Factors Influencing Logistics Service Business for Improving The 20- Years Performance National Strategies Plan - Rathachatranont, Wanlop (Arts of Management Journal, 2024)
The objectives of this research were: 1). To study the innovation level of the organization, management, logistics, and brand value of the organization and operating results of logistics service businesses in Thailand. 2). to study the causal relationships between organizational innovation, logistics management, and organizational brand values. 3). to verify the causal relationship between organizational innovation, logistics management, and organizational brand. The sample group is high-level executives and above in Thailand’s logistics service companies that passed the standard, totaling 372 people/company. The research instrument was a questionnaire. Data were analyzed using structural equation modeling. The results of the study found that overall, the sample group had an opinion on organizational innovation at a high level ( = 3.91), has an opinion on logistics management at a high level ( = 4.02), and an opinion on the brand value of the organization at a high level. ( = 3.98) The sample group has a high level of opinion on the performance of the organization ( = 3.92). Analysis of the relationship between the variables of management, logistics, and brand value of the organization, and organizational performance of 11 variables. It was found that all variables had a positive relationship in the same direction. The correlation coefficient was between 0.200 and 0.731 and the relationship was at a low to high level. Structural equation simulation models have index values. Statistical consistency 2/df =1.34, p =0.09, CFI =0.97, TLI =0.96, GFI =0.94, AGFI =0.98 which is greater than 0.900, RMSEA =0.05 which is less than 0.08 and RMR =0.01 which is smaller than 0.05, so it can be concluded that the model is consistent with the empirical data and is consistent with the research hypotheses that have been established. Logistics management has a direct influence on the performance of the logistics service business. Logistics management in Thailand has an indirect influence on the performance of logistics service businesses in Thailand through the brand value of the organization.